LFA-1 cluster formation in T-cells depends on L-plastin phosphorylation regulated by P90RSK and PP2A - Wabnitz, Guido H.; Honus, Sibylle; Habicht, Jüri; Orlik, Christian; Kirchgessner, Henning; Samstag, Yvonne (Cellular and molecular life sciences, 2021)
The integrin LFA-1 is crucial for T-cell/ APC interactions and sensitive recognition of antigens. Precise nanoscale organization and valency regulation of LFA-1 are mandatory for an appropriate function of the immune system. While the inside-out signals regulating the LFA-1 affinity are well described, the molecular mechanisms controlling LFA-1 avidity are still not fully understood. Here, we show that activation of the actin-bundling protein L-plastin (LPL) through phosphorylation at serine-5 enables the formation of clusters containing LFA-1 in high-affinity conformation. Phosphorylation of LPL is induced by an nPKC-MEK-p90RSK pathway and counter-regulated by the serine-threonine phosphatase PP2A. Interestingly, recruitment of LFA-1 into the T-cell/APC contact zone is not affected by LPL phosphorylation. Instead, for this process, activation of the actin-remodeling protein cofilin through dephosphorylation is essential. Together, this study reveals a dichotomic spatial regulation of LFA-1 clustering and microscale movement in T-cells by two different actin-binding proteins, LPL and cofilin.